2006
DOI: 10.1007/1-4020-3450-4_12
|View full text |Cite
|
Sign up to set email alerts
|

Image of Optical Diffraction Radiation (Odr) Source and Spatial Resolution of Odr Beam Profile Monitor

Abstract: The approach to obtain the image shape of an optical diffraction radiation (ODR) source focused by lens on a detector with taking into account the "pre-wave zone" effect has been developed. In full analogy with optical transition radiation source the characteristic size of ODR slit image doesn't depend on the Lorentz-factor and is defined by slit width, wavelength and lens aperture.If a beam is passed through a narrow slit the shape of a slit image depends on a beam size. ODR generated by extremely ultrarelati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…In accordance with approach developed in [7] one may obtain the following expressions for both polarized components of a field on a target surface:…”
Section: Approachmentioning
confidence: 92%
See 1 more Smart Citation
“…In accordance with approach developed in [7] one may obtain the following expressions for both polarized components of a field on a target surface:…”
Section: Approachmentioning
confidence: 92%
“…Following [7] let us consider the image of an ODR source with regard to the ''pre-wave zone" effect. For simplification of calculations let us consider backward diffraction radiation (BDR) for a perpendicular particle passing near the target.…”
Section: Approachmentioning
confidence: 99%
“…(6) can be carried out analytically in polar coordinates as shown in Refs. [11][12][13][14][15]. The electric field in the image plane can be written as…”
Section: Theoretical Modelmentioning
confidence: 99%
“…[12] Castellano and Verzilov investigated the SPF characteristics in the case of ideal imaging. Further investigations were carried out by Potylitsyn [13] who studied the influence of the prewave zone effect on the OTR SPF, and by Xiang and Huang [14] who investigated some aspects of the beam imaging resolution. The first systematic resolution study of an OTR based beam profile monitor in view of a dedicated application was made by Kube in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The PSF describes the image of a point source, i.e., the image of a single electron in the case of OTR generation. The OTR PSF was investigated for the first time by Castellano and Verzilov [14], and later in more detail by Potylitsyn [15], Xiang and Huang [16], and Kube [17]. It was shown that the PSF has a double-lobe structure defined by the radiation wavelength, the acceptance of the optical system, and the alignment accuracy.…”
Section: Introductionmentioning
confidence: 99%